Comprehensive Dental Management Of Diabetic Patients: Coordinated Preventive, Diagnostic, And Educational Roles Of Dental Teams (The Review of Diabetic Studies, 2025)
Background:Diabetes mellitus is strongly associated with a wide spectrum of oral complications, including periodontal disease, xerostomia, impaired wound healing, and oral infections. These manifestations reflect underlying metabolic, vascular, and immunological disturbances, positioning dental teams as essential partners in the long-term management of diabetic patients.Objective:This narrative review synthesizes evidence from more than fifty peer-reviewed studies to examine how coordinated preventive, diagnostic, and educational interventions delivered by dentists, dental assistants, and dental hygienists can improve oral and systemic outcomes in individuals with diabetes.Methods:A narrative synthesis approach was used to integrate findings from epidemiological research, clinical trials, mechanistic studies, and professional guidelines. The review focuses on the bidirectional relationship between diabetes and oral disease, early oral indicators of glycemic instability, and evidence-based strategies for comprehensive dental management.Results:The literature consistently demonstrates that diabetic patients experience accelerated periodontal destruction, salivary dysfunction, increased susceptibility to infection, and delayed postoperative healing. Dental teams play a critical role in early detection of metabolic imbalance, reinforcing patient self-care, and reducing oral inflammatory burden through structured preventive care. Coordinated workflows—combining periodontal therapy, patient education, metabolic assessment, and interprofessional communication—contribute to improved glycemic control and better overall health outcomes.Conclusion:Comprehensive dental management is a central component of chronic disease care for individuals with diabetes. Integrated, team-based approaches involving dentists, dental assistants, and hygienists enhance diagnostic accuracy, support long-term behavioral change, and mitigate both oral and systemic complications. Future research should prioritize interprofessional care models, assistant-led education strategies, and region-specific studies—particularly in high-prevalence settings such as Saudi Arabia—to optimize outcomes and strengthen evidence-based guidelines.